2014
DOI: 10.1590/s0100-736x2014000100006
|View full text |Cite
|
Sign up to set email alerts
|

The importance of Leptospira interrogans serovars Icterohaemorrhagiae and Canicola in coastal zone and in southern fields of Rio Grande do Sul, Brazil

Abstract: This study aimed to describe the occurrence of Leptospira interrogans serovars Icterohaemorrhagiae and Canicola, in coastal zone and in southern grasslands of Rio Grande do Sul, Brazil. In each one of the four analyzed farms blood samples were collected from free-living wild animals, domestic animals and humans to perform serological testing for leptospirosis. The presence of antibodies was verified by microscopic agglutination test (MAT). The criterion adopted to consider a serum as agglutination reactant was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
2
Order By: Relevance
“…Outros importantes sorogrupos foram o Grippotyphosa, o mais reativo no Maranhão (Carvalho et al, 2014), e Icterohaemorrhagiae que destacam a necessidade da inclusão de programas de desratização junto às propriedades uma vez que os principais hospedeiros de manutenção de ambos são o rato (Rattus norvegivus), onde a presença desses reservatórios, indica as deficientes práticas sanitárias, tais como: o acúmulo de lixo e resíduos orgânicos, falta de higiene nos comedouros e bebedouros, mau armazenamento dos alimentos, negligência com a qualidade da água, proliferação de animais sinantrópicos e silvestres de vida livre em torno das propriedades, estreitando seu contato com animais domésticos e o homem (Silva et al, 2014). O sorogrupo Autumnalis, que possui alta frequência nos estudos da região Nordeste (Azevedo et al, 2004;Higino et al, 2010;Melo et al, 2010;Alves et al, 2012;Pereira et al, 2018) e geralmente associado à presença de animais silvestres e criatórios próximos a reservas florestais, apresentou baixa ocorrência nos rebanhos Sergipanos (2,66%), mesmo com 80% dos criadores relatando a circulação de animais silvestres no entorno das propriedade.…”
Section: Resultsunclassified
“…Outros importantes sorogrupos foram o Grippotyphosa, o mais reativo no Maranhão (Carvalho et al, 2014), e Icterohaemorrhagiae que destacam a necessidade da inclusão de programas de desratização junto às propriedades uma vez que os principais hospedeiros de manutenção de ambos são o rato (Rattus norvegivus), onde a presença desses reservatórios, indica as deficientes práticas sanitárias, tais como: o acúmulo de lixo e resíduos orgânicos, falta de higiene nos comedouros e bebedouros, mau armazenamento dos alimentos, negligência com a qualidade da água, proliferação de animais sinantrópicos e silvestres de vida livre em torno das propriedades, estreitando seu contato com animais domésticos e o homem (Silva et al, 2014). O sorogrupo Autumnalis, que possui alta frequência nos estudos da região Nordeste (Azevedo et al, 2004;Higino et al, 2010;Melo et al, 2010;Alves et al, 2012;Pereira et al, 2018) e geralmente associado à presença de animais silvestres e criatórios próximos a reservas florestais, apresentou baixa ocorrência nos rebanhos Sergipanos (2,66%), mesmo com 80% dos criadores relatando a circulação de animais silvestres no entorno das propriedade.…”
Section: Resultsunclassified
“…This investigation provides an important initial epidemiological step in attempting to understand the locations and infection patterns of the various serogroups for this neglected disease. Previous studies have identified the importance of serogroups Canicola and Icterohaemorrhagiae for livestock production in the state, along with serogroups Australis, Autumnalis, Bratislava, Copenhageni, Grippotyphosa, Pyrogenes, and Tarassovi for bovines [21,22]. Other studies focusing on animal production in the southeast area of Rio Grande do Sul also identified a large variety of serogroups present [23].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these reservoirs, which were reported by 63.41% (26/41) of the goat owners in Sergipe, is usually associated with poor sanitation practices such as the accumulation of waste, lack of hygiene during food and water handling, poor food storage practices, poor water quality, and presence of wild and synanthropic animals around the properties, favoring the increased contact of these animals with livestock and humans (SILVA et al, 2014). As a result, the facilities are constantly exposed to the etiological agent via the urine of infected animals, particularly in still water because it favors the survival of bacteria in the environment (GOMES, 2013).…”
Section: Discussionmentioning
confidence: 99%